Locally-tailored vs. centrally-administered strategies for implementation of primary human papillomavirus (HPV) screening in an integrated healthcare system: a qualitative research study - Erin E. Hahn; Erin E. Hahn; Corrine Munoz-Plaza; Chunyi Hsu; Nancy T. Cannizzaro; Quyen Ngo-Metzger; Michael K. Gould; Brian S. Mittman; Melissa Hodeib; Devansu Tewari; Chun R. Chao; Chun R. Chao (Frontiers in Health Services)
IntroductionPrimary human papillomavirus(HPV) testing is recommended for cervical cancer screening for women aged 30–65 years without a history of abnormal results. However, there is little clear guidance regarding effective strategies for implementing primary HPV screening. As part of an ongoing randomized trial comparing implementation strategies for primary HPV testing (a centrally administered + usual care strategy vs. centrally administered + locally tailored strategy), we evaluated clinician experiences and perceptions of large-scale implementation of primary HPV screening in an integrated healthcare system, Kaiser Permanente Southern California.Materials and methodsWe conducted qualitative interviews with internal medicine, family medicine and obstetrics/gynecology clinicians to gain insight into fidelity to the interventions and implementation strategies, barriers and facilitators to implementation, and recommendations. Participants from both arms of the trial were recruited. Interview guides were developed with the Consolidated Framework for Implementation Research (CFIR). We recruited physicians, licensed vocational nurses, and medical assistants after primary HPV screening had been implemented. Interviews were recorded and transcribed. Using a team coding approach, we developed an initial coding structure refined during iterative analysis; data were subsequently organized thematically into domains, key themes, and sub-themes using thematic analysis, followed by framework analysis informed by CFIR.ResultsThirty-two interviews were conducted. Participants in both arms of the trial noted high awareness, preparedness, buy-in, and fidelity to the new screening process. Initial barriers concerned specimen collection, proper ordering, and lab delays. An unanticipated barrier was the length of time needed to return lab results for reflexive cytology tests after a positive HPV result which reportedly increased patient anxiety. Participants in both arms reported fidelity to the centralized strategy (e.g., attending webinars, leadership announcements). In the local-tailored arm, few participants recalled the local-tailored resources.DiscussionThe centralized strategy was perceived as highly acceptable and feasible, and fidelity to the associated interventions appear to be facilitators of practice change. Recommendations for improving implementation included patient education, outreach and ongoing clinician training. Findings can be applied to other health systems and settings considering primary HPV screening implementation, particularly those within the U.S. or with a similar health care model. Trial RegistrationClinicalTrials.gov, identifier #NCT04371887